The alpha-actinin-3 r577x polymorphism and physical performance in soccer players - Coelho, D. B.; Pimenta, E.; Rosse, I. C.; Veneroso, C.; Becker, L. K.; Carvalho, M.-R. S.; Pussieldi, G.; Silami-Garcia, E. (The Journal of Sports Medicine and Physical Fitness, 2016)
The aim of this study was to investigate the association between ACTN3 genotype (RR, RX, and XX) and physical performance of 138 adult, professional, U-20 and U-17 years Brazilian first-division soccer players. The following three parameters were investigated: first, speed, using a 30--m sprint test with speed measured at 10 m, 20 m, and 30 m; second, muscular strength, using counter-movement-jump and squat jump tests; and third, aerobic endurance using the Yo-Yo endurance test. The athletes were ranked in ascending order according to their performance in each test. after which they were divided into quartiles and clustered according to genotype and allele frequency. The X 2 was used to compare the genotype frequencies (RR, RX and RR) and allele frequencies (R and X) within and between the different quartiles of performance rating. No significant differences were observed in genotypic or allelic frequencies between different performance ratings. The ACTN3 genotype was not associated to any of the physical performance parameters. This information should be noted with care, because, besides physical capacity, there are other factors, like tactical knowledge, that interfere with performance in sport, considering that expertise is multifactorial.